Keunggulan Penyelesaian Sengketa Alternatif Dibandingkan dengan Litigasi di Pengadilan - Nugroho, Lucky Dafira; Putri, Meila Maulidina Eka; Masyunah, Masyunah (AHKAM, 2025)
Alternative Dispute Resolution (ADR) has increasingly gained attention as an efficient method for resolving conflicts outside formal litigation channels. This study aims to analyze the advantages of ADR compared to court litigation through a normative juridical approach, using data collected from literature review. The findings indicate that ADR offers several advantages, including time and cost efficiency, procedural flexibility, privacy protection for the parties involved, and the ability to preserve relationships after disputes. In Indonesia, ADR has received legal recognition through Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. However, its implementation still faces challenges such as limited public awareness of ADR, a shortage of competent practitioners, the dominance of litigation culture, and limitations in infrastructure and technological access. To overcome these obstacles and enhance the effectiveness of ADR, systematic efforts are needed, including practitioner competency development, regulatory strengthening, supporting infrastructure development, legal culture transformation, and international cooperation. These findings affirm that, with strategic optimization, ADR has the potential to become a primary solution for establishing faster, more cost-effective, and restorative justice–oriented dispute resolution mechanisms in Indonesia.